A randomized trial to compare the safety and efficacy of two ranibizumab dosing regimens in a Turkish cohort of patients with choroidal neovascularization secondary to AMD. (27th August 2014) - Eldem, Bora M.; Muftuoglu, Gulipek; Topbaş, Seyhan; Çakir, Mehmet; Kadayifcilar, Sibel; Özmert, Emin; Bahçecioğlu, Halil; Sahin, Feride; Sevgi, Serhan; the SALUTE study group
Abstract Purpose To compare visual outcomes, number of visits and ranibizumab injections in patients treated with a Wait & Extend (W&E) or Treat & Observe (T&O) regimen. Methods This 12‐month, randomized, multicentre, open‐label study enrolled patients aged ≥50 years with choroidal neovascularization (CNV) secondary to AMD who had not received anti‐VEGF agents. Patients received three monthly injections of ranibizumab before randomization (1:1): (i) T&O patients were examined monthly and retreated if needed, (ii) W&E patients had a follow‐up visit 1 month later. If no lesions were active, the interval to the next visit was extended by 2 weeks to a maximum of 8 weeks. Active lesions were re‐treated and the follow‐up schedule restarted. Primary end‐point was change in BCVA at Month 12. Results Of the 104 screened patients, 99 were eligible and received ≥1 ranibizumab injection; 93 were randomized (T&O: 45, W&E: 48). The median (interquartile range [IQR]) change in BCVA (logMAR) from baseline at Month 12 was similar between groups (T&O: −0.12 [0.38]; W&E: −0.18 [0.32], p = 0.267). Median (IQR) number of visits at study end (including screening, baseline and control visit after 1st injection) was 15.0 (1.0) for T&O, and 12.0 (2.0) for W&E (p < 0.001). Injection numbers were similar between groups (median [IQR]: 6.0 [3.0] and 5.0 [4.0], respectively, p = 0.215). Adverse events were similar between groups. Conclusion W&E regimen resulted in a similar efficacy and safety profile to the labelled T&O regimen in patients with CNV secondary to AMD, and may help reduce the burden of follow‐up visits.